2006
DOI: 10.1104/pp.106.079418
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Analysis of mRNA Translation States during Sucrose Starvation in Arabidopsis Cells Identifies Cell Proliferation and Chromatin Structure as Targets of Translational Control

Abstract: Sucrose starvation of Arabidopsis (Arabidopsis thaliana) cell culture was used to identify translationally regulated genes by DNA microarray analysis. Cells were starved by subculture without sucrose, and total and polysomal RNA was extracted between 6 and 48 h. Probes were derived from both RNA populations and used to screen oligonucleotide microarrays. Out of 25,607 screened genes, 224 were found to be differentially accumulated in polysomal RNA following starvation and 21 were found to be invariant in polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 45 publications
5
85
0
Order By: Relevance
“…The TRAP-RF data showed the same phenomena. This indicates that hypoxia influences uORF translation and reconfirms that hypoxia reduces ribosomal protein mRNA translation, as seen in response to several other energy-limiting conditions (6,8,12,18,21).…”
Section: Hypoxia Reduces Ribosome Protection Associated With Initiatimentioning
confidence: 79%
See 1 more Smart Citation
“…The TRAP-RF data showed the same phenomena. This indicates that hypoxia influences uORF translation and reconfirms that hypoxia reduces ribosomal protein mRNA translation, as seen in response to several other energy-limiting conditions (6,8,12,18,21).…”
Section: Hypoxia Reduces Ribosome Protection Associated With Initiatimentioning
confidence: 79%
“…The translational status of individual transcripts is regulated by diverse environmental stimuli, including carbon availability (8,9), cold (10, 11), dehydration (6, 10, 12), excess cadmium (13), heat (14), hypoxia (7,15), pathogens (16), photomorphogenic illumination (17), reillumination (18), salinity (10), singlet oxygen (19), symbionts (20), and unanticipated darkness (21). Translation is also modulated by regulatory molecules, including auxin (22,23), gibberellins (24), and polyamines (25).…”
mentioning
confidence: 99%
“…Furthermore, AtHDA19 antagonizes the histone acetyltransferase AtGCN5 in regulating the maintenance of embryo axis formation and light-responsive gene expression, respectively (Benhamed et al, 2006;Long et al, 2006). Besides development, AtHDA19 is required for jasmonic acid-and ethylene-mediated plant responses to plant pathogens, for responses of cultured cells to sucrose starvation and for transcriptional repression in response to abscisic acid, drought and salt stress (Song et al, 2005;Zhou et al, 2005;Nicolai et al, 2006;Song and Galbraith, 2006). The latter response is likely executed by an AtHDA19/SIN3 repressor complex that is recruited to target genes via ethyleneresponsive element binding factors (ERFs) (Song et al, 2005;Song and Galbraith, 2006).…”
Section: Arabidopsis Hdacsmentioning
confidence: 99%
“…For example, high levels of expression of one Arabidopsis L11 gene (RPL11C, previously called RPL16B) was observed in shoot and primary root meristems and lateral root primordia in response to auxin treatment, whereas expression of another L11 gene (RPL11A, previously called RPL16A) showed more cell-type specific gene expression (Williams and Sussex 1995). More recently, global studies of translational control have confirmed that r-protein mRNAs are highly regulated at the translational level (Branco-Price et al 2005Kawaguchi et al 2004;Kawaguchi and Bailey-Serres 2005;Nicolaï et al 2006). From these analyses, it appears that r-protein expression in plants may be regulated at the transcriptional and posttranscriptional levels.…”
Section: Mitochondrial Ribosomesmentioning
confidence: 96%